2010
DOI: 10.1097/coc.0b013e3181aaca87
|View full text |Cite
|
Sign up to set email alerts
|

Wide Excision or Mohs Micrographic Surgery for the Treatment of Primary Dermatofibrosarcoma Protuberans

Abstract: From a surgical standpoint, WE was faster than MMS and resulted in a less complex defect/closure. Although positive margin resection was more common with WE, local control was ultimately similar for the 2 surgical modalities. The choice of WE versus MMS should be based on individualized patients/tumor characteristics and institutional expertise in these modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 23 publications
1
88
0
4
Order By: Relevance
“…Conversely, obtaining negative lateral margins is more difficult with WLE compared with MMS, as the neoplastic projections in DFSP can extend up to 3 cm beyond clinically visible borders of the lesion. [11][12][13] A multidisciplinary approach to DFSP has been described for select lesions (ie, head and neck) not amendable to WLE or MMS alone. Although this multidisciplinary approach has been associated with favorable recurrence rates and reconstructive outcomes, there have been few reports exclusively using this method for the management of all DFSP lesions.…”
mentioning
confidence: 99%
“…Conversely, obtaining negative lateral margins is more difficult with WLE compared with MMS, as the neoplastic projections in DFSP can extend up to 3 cm beyond clinically visible borders of the lesion. [11][12][13] A multidisciplinary approach to DFSP has been described for select lesions (ie, head and neck) not amendable to WLE or MMS alone. Although this multidisciplinary approach has been associated with favorable recurrence rates and reconstructive outcomes, there have been few reports exclusively using this method for the management of all DFSP lesions.…”
mentioning
confidence: 99%
“…29 Meguerditchian et al found higher rates of recurrence after wide excision than after MMS, but the difference was not significant because the numbers were too low. 30 Chaput et al found that with MMS, most patients needed one operation (72%) with median clinical excision margins of 17 mm, and only direct closure was required. 31 They particularly advocated the technique for lesions on the head and neck as it is essential to spare as much tissue as possible.…”
Section: Dermatofibrosarcoma Protuberansmentioning
confidence: 98%
“…26,54 The concept of completely evaluating the deep and circumferential margins during MMS cannot be overstated and obviously greatly decreases the recurrence rate. 26 There is a role for MMS in treating LMS and DFSP at certain anatomic sites such as the face, hands, and feet, in order to conserve tissue, improve cosmetic deformity, as well as limit functional deficit/morbidity.…”
Section: Management Optionsmentioning
confidence: 99%